Archaeological mitogenomes illuminate the historical ecology of sea otters (Enhydra lutris) and the viability of reintroduction. Issue 1940 (9th December 2020) - Wellman, Hannah P.; Austin, Rita M.; Dagtas, Nihan D.; Moss, Madonna L.; Rick, Torben C.; Hofman, Courtney A.
Abstract : Genetic analyses are an important contribution to wildlife reintroductions, particularly in the modern context of extirpations and ecological destruction. To address the complex historical ecology of the sea otter ( Enhydra lutris ) and its failed 1970s reintroduction to coastal Oregon, we compared mitochondrial genomes of pre-extirpation Oregon sea otters to extant and historical populations across the range. We sequenced, to our knowledge, the first complete ancient mitogenomes from archaeological Oregon sea otter dentine and historical sea otter dental calculus. Archaeological Oregon sea otters ( n = 20) represent 10 haplotypes, which cluster with haplotypes from Alaska, Washington and British Columbia, and exhibit a clear division from California haplotypes. Our results suggest that extant northern populations are appropriate for future reintroduction efforts. This project demonstrates the feasibility of mitogenome capture and sequencing from non-human dental calculus and the diverse applications of ancient DNA analyses to pressing ecological and conservation topics and the management of at-risk/extirpated species.